2006
DOI: 10.1002/hed.20445
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ultrasonically activated shears in thyroid surgery

Abstract: The use of UAS in thyroid surgery is a safe method for hemostasis, as well as for the division of blood vessels and thyroid tissue. It leads to the reduction of the total operative time without serious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 22 publications
3
27
1
2
Order By: Relevance
“…In experienced hands the rate of this complication is lower than 2% [10]. In line with previous studies, the use of a UHS did not increase the RLN palsy risk in our study [7,10,12]. The rate of transient hypocalceamia has been reported as %5-%15 and permanent hypocalcemia rates have been reported as %5 in total thyroidectomoies [12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In experienced hands the rate of this complication is lower than 2% [10]. In line with previous studies, the use of a UHS did not increase the RLN palsy risk in our study [7,10,12]. The rate of transient hypocalceamia has been reported as %5-%15 and permanent hypocalcemia rates have been reported as %5 in total thyroidectomoies [12].…”
Section: Discussionsupporting
confidence: 90%
“…We calculated blood loss from the increase in weight of the blooded gauzes. Some authors have reported that the amount of bleeding did not differ between the two methods [7,12,13]. Also Defechereux et al5 reported a reduction in intra-operative bleeding.…”
Section: Discussionmentioning
confidence: 95%
“…Tiroidektomide Harmonic Scalpel son yıllarda yaygın olarak kullanılmakta olup etkinliği ile ilgili bir çok çalışma yapılmıştır (3,4,6,7,(9)(10)(11)(12)(13)(14). Harmonic Scalpel'ın kolay kullanımı ve manipülasyonu, diseksiyon, kesme ve koagülas-yon işlemini aynı anda yapabilmesi nedeniyle operasyon süresini kısalttığı bildirilmiş ve bununda cihazın en önemli avantajı olduğu vurgulanmıştır (6,7,(15)(16)(17) (10,18,19,22).…”
Section: Discussionunclassified
“…Kalıcı hipokalsemi ise paratiroid bezlerin çıkarılması ya da devaskularizasyonu sonucu oluşur. Tiroidektomi sonrası kalıcı hipokalsemi %0,3-3 ve geçici hipokalsemi %1,6-30 arasın-da bildirilmektedir (23)(24)(25)(26)28 Bazı yazarlar Harmonic Scalpel kullanımının drenaj miktarını değiştirmediğini belirtmişler (4,12,14). Bunun aksine yapılan birkaç çalışmada da tiroidektomide Harmonic Scalpel kullanımı postoperatif drenaj miktarını azalttığı belirtilmiştir (6,7,17,22).…”
Section: Discussionunclassified
“…The use of ultrasonic's tweezers result in reduction of 15-20% for operatory time and has excellent cost/benefit ratio compared with the conventional technique 8 . In pulmonary lobectomies for example these costs are decreased in 30.8% when considering its use 5 . Studies of surgical time on hemorroidectomy showed that the operation time is significantly reduced with the use of high precision tweezers for cutting and coagulation in relation to the use of conventional knives.…”
Section: Introductionmentioning
confidence: 99%